1993
DOI: 10.1088/0953-8984/5/7/013
|View full text |Cite
|
Sign up to set email alerts
|

Local s, p and d charge distributions and X-ray emission bands of SiO2: alpha -quartz and stishovite

Abstract: Aktml. An experimental and theoretical study of the electronic structure and the x-ray Si K and Si L emission bands of 42aoordinated @ q u a m and 63-coordinated slishovite is presented. The nature of atomic states participating in the x-ray valence band spectra is idcntified. In particular the longstanding controversy a b u t the mle of Si M-like states is analysed; evidently, Si M-like electrons essentially contribute 10 the intensity of Si L emission bands We have calculated the total density of states, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The role played by d-orbitals in Si± ±O bond formation is a controversial problem (Gibbs, Downs, Boisen, 1994, Simunek, Vackar, Wiech, 1993. The electron emission spectra about a-quartz and stishovite have been analyzed by Wiech (1984).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role played by d-orbitals in Si± ±O bond formation is a controversial problem (Gibbs, Downs, Boisen, 1994, Simunek, Vackar, Wiech, 1993. The electron emission spectra about a-quartz and stishovite have been analyzed by Wiech (1984).…”
Section: Resultsmentioning
confidence: 99%
“…The electron emission spectra about a-quartz and stishovite have been analyzed by Wiech (1984). Simunek et al (1993) have concluded that Si 3d-orbital does not participate in the Si± ±O bond. The Si K-and Si L-emission bands reflect the Si p-like and Si s/d-like electrons of the valence band, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The bonding electrons observed from X-ray diffraction study are interpreted by the optimized pair potential and molecular orbital calculation (Svane & Antoncik, 1987;Mimaki et al, 2000). The electron orbital overlapping and the bonding energy render the deformation of MO 6 octahedra of rutile-type structures from the bond character (Baur & Khan, 1971;Simunek et al, 1993;Camargo et al, 1996;Gibbs et al, 1997Gibbs et al, , 1998. The structure change with pressure is characterized by the molecular orbital overlapping with the metal-metal interaction.…”
Section: Valence Electrons Of C-sio 2 Under High Pressurementioning
confidence: 99%
“…This is typical of SiO 2 13,15 and in agreement with local and partial Si 3p state calculations of SiO 2 . 16,17 When decreasing the excitation energy, i.e. when probing silica thicknesses closer to the interface with Mo, changes are seen towards higher photon energies: the intensity of the structures increases, leading to a shift and a broadening of the spectral density.…”
Section: Silicon 3p Statesmentioning
confidence: 99%
“…At 3 keV, when the entire SiO 2 layer is analysed, the O 2p density is characteristic of silica 12 and in agreement with the theoretical density of states. 16,17 The band has its maximum at 526.9 eV and is asymmetrical towards the lower photon energies. The structure at ¾521.7 eV is due to the second-order Na K˛emission coming from surface contamination.…”
Section: Oxygen 2p Statesmentioning
confidence: 99%